2009
DOI: 10.1536/ihj.50.267
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils May Be Involved in Thrombus Growth in Acute Coronary Syndrome Histologic Examination of Aspiration Samples

Abstract: SummaryThrombus aspiration therapy allows for the examination of thrombus and atheroma fragments in acute coronary syndrome (ACS). Inflammatory cells and platelet activation play key roles in thrombus formation in ACS. However, histopathologic evaluation of thrombi in ACS has not been adequately addressed. We performed histologic analysis of tissue samples obtained by thrombus aspiration therapy. We studied 165 samples from patients with ACS. The area of each sample, percentage of red thrombus, and percentage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 29 publications
0
46
0
1
Order By: Relevance
“…7,14 Some studies reported that EC is related to vasospastic angina pectoris and large thrombus formation. 15 A connection may exist between EC and vasculogenic events due to the strong vasoconstrictor, procoagulant, and local inflammatory effects of eosinophils. We included EC, PC, and MPV counts as suspected predictive factors demonstrating platelet activation in our study.…”
Section: -13mentioning
confidence: 99%
“…7,14 Some studies reported that EC is related to vasospastic angina pectoris and large thrombus formation. 15 A connection may exist between EC and vasculogenic events due to the strong vasoconstrictor, procoagulant, and local inflammatory effects of eosinophils. We included EC, PC, and MPV counts as suspected predictive factors demonstrating platelet activation in our study.…”
Section: -13mentioning
confidence: 99%
“…At the time of plaque disruption, locally released tissue factor-positive and leukocyte-derived MPs play an important role in fibrin-rich thrombus formation [35][36][37][38][39][40][41][42] . Moreover, activated inflammatory cells, such as neutrophils, macrophages and eosinophils, contribute to the growth of a thrombus 17,89,90) . Our study also demonstrated that erythrocyte-rich thrombi often contain more inflammatory cells, such as MPO-positive neutrophils, thus leading to increased plasma MPO levels, which reflects a high thrombus burden 78,84) .…”
Section: )mentioning
confidence: 99%
“…5,6 Importantly, eosinophils have been recently involved in thrombus growth and coronary vasospasm. 7,8 Of note, we reported that higher eosinophil cationic protein (ECP) levels were associated to the atherosclerotic burden and to a worse prognosis in patients undergoing stent implantation. 9,10 Moreover, in a postmortem study, eosinophil infiltration was found at the site of late drug-eluting stent thrombosis.…”
mentioning
confidence: 99%